The Relationship between Attitude and Knowledge of Urban Farming among Community in Pandemic Covid-19 - Nurma Zela Gustina; Widyatuti Widyatuti (Global Health Science Group, 2021)
Efforts to prevent the transmission of Covid-19 are not only sufficient by implementing health protocols. Need increase immunity to prevent Covid-19 such as consuming vegetables. Urban farming is a solution for people in urban areas to take advantage of the minimal yards by growing vegetables. The urban farming program is a planting program in urban areas using minimal land. Pandemic situation requires community to implement health protocol, which one is reduce mobility. This restriction has impact on decrease of market operation as a place to buy vegetables, as well as the prices of staple during pandemic can exacerbating this situation. This study aims to determine the relationship between attitudes and knowledge of the people in the Tanah Baru Depok. This study is a cross sectional study with 32 respondents taken by total sampling. Data were collected using online questionnaire given to respondent. Data analysis in this study used the chi square test. The results showed that there was a relationship between people's attitudes towards the urban farming program during the Covid-19 pandemic with p value = 0.004 (p <0.05) and it was known that there was a relationship between public knowledge of the urban farming program during the pandemic with a p value of 0.000 ( p <0.05). Based on the results of this study, it is necessary to increase the extension of the urban farming program carried out by community nurses to be able to increase health education of vegetable consumption during the Covid-19 pandemic to protect families from exposure to Covid-19.